Peranan Literasi Keuangan Dalam Meningkatkan Financial Skill Pada Mahasiswa Ekonomi Syariah Angkatan 2022 Iain Sorong - Lita Desiana.F; La Ode Obi; Nur Aisyah Indarningsih (At-Thariqah: Jurnal Ekonomi, 2025)
This study aims to explore the role of financial literacy among students to enhance the financial skills of Sharia economics students of the 2022 batch. This research uses qualitative research methods with a descriptive approach. Data collection methods include observation, interviews, and documentation. The respondents in this study are Sharia economics students from the 2022 batch. Data were obtained through interviews with eight informants. The data analysis was conducted by data reduction, data presentation, and drawing conclusions, and the data validity test used by the researcher is data triangulation. Where this study conducted data analysis with data reduction, data presentation, and drawing conclusions, the data validity test used by the researcher was data triangulation. The results of this study indicate that financial literacy plays a role in improving students' financial skills, divided into several stages. These stages are the stages of determining sources of funds, using funds, and planning for the future. Another finding in this study is by providing opportunities in the form of education that can improve students' financial skills with seminars or workshops on an ongoing basis, and providing more relevant and practical learning subjects. Therefore, an integrated financial literacy education strategy is needed between academic institutes and students so that financial literacy can be improved sustainably